Antioxidative NAC-Loaded Silk Nanoparticles with Opening Mucosal Tight Junctions for Nasal Drug Delivery: An In Vitro and In Vivo Study - Tze-Wen Chung; Ting-Ya Wu; Zheng-Yu Siah; Der-Zen Liu (MDPI AG, 2022)
Using nasal routes to deliver drugs to the brain using multifunctional nanoparticles (NPs) to bypass the blood-brain barrier (BBB) might enhance the delivery efficacy. Anti-oxidative N-Acetyl-L-cysteine (NAC)-loaded silk fibroin (SF/NAC) NPs are produced, characterized and studied as a potential delivery vehicle for NAC delivered to the brain via nasal for both in vitro and in vivo studies. The NPs are not cytotoxic to RPMI 2650 cells, mucosal model cells, at a concentration of 6000 μg/mL. The anti-oxidative activities of SF/NAC NPs are demonstrated by high H2O2 scavenge capacities of the NPs and shown by mitochondrial superoxide (MitoSOX) immunostaining of human mesenchymal stem cells. Tight junctions in RPMI 2650 cells are opened after 30 min of incubation with SF/NAC NPs, which are demonstrated by measuring the decrease in trans-epithelial electrical resistance (TEER) values and discreteness in ZO-1 stains. The cellular uptake of SF/NAC NPs by RPMI 2650 cells is significantly greater than that for SF NPs and increased with increasing incubation time. In an in vivo imaging study (IVIS) using rats shows that the amount of NAC that is delivered to the brain by SF/NAC NPs increased by 1.40-2.60 times and NAC is retained longer in the nasal cavity than NAC solutions in a 2-h study.